Association between mealtimes of first and last meals and food consumption in pregnant women (Research, Society and Development, 2022)
Eating an early first meal and a tendency towards morningness have been associated with healthy eating habits. The objective of the study was to investigate the association between mealtimes of first and last meals and food consumption of pregnant women. Methods: A cross-sectional study with 111 pregnant women who use a public health service. Sociodemographic, nutritional and health data were collected from medical records. Food consumption was assessed by habitual dietary intake. Nutritional value was determined with the DietPro® program (version 6.1) and diet quality was assessed through Diet Quality Index Adapted for Brazilian Pregnant Women (IQDAG).. The study was approved by the Research Ethics Committee of Universidade Federal de Viçosa (No. 4.098.560). Results: The mean age was 34.3 (±5.5) years. Pregnant women who had a late first meal and an early last meal (PR:2.55; 95% CI 1.41-4.63) presented a higher prevalence of vitamin B12 deficiency. On the other hand, pregnant women who had a late first meal and an early last meal (PR:4.74; 95%CI 1.50-15.04), and those who had  late first and last meals  (PR:4.31; 95%CI 1.37; 13.58), presented a higher prevalence of having an inadequate number of meals. Conclusion: Pregnant women who eat late have a higher prevalence of vitamin B12 deficiency and eating ≤3 meals during the day compared to those who eat early. The result reinforces the need for approaches to prenatal care based on mealtimes and nutrition aimed at improving the dietary profile of this population.